Rút gọn biểu thức a, (x + y)^2 + (x – y)^2 b, 2(x – y)(x + y) + (x + y)^2 + (x – y)^2 c, (x – y + z)^2 + (z – y)^2 + 2(x – y + z)(y – z)

Question

Rút gọn biểu thức
a, (x + y)^2 + (x – y)^2
b, 2(x – y)(x + y) + (x + y)^2 + (x – y)^2
c, (x – y + z)^2 + (z – y)^2 + 2(x – y + z)(y – z)

in progress 0
Alice 1 tháng 2021-08-31T06:20:02+00:00 2 Answers 12 views 0

Answers ( )

    0
    2021-08-31T06:21:22+00:00

    a, (x+y)² + (x–y)²

    = (x²+2xy+y²)+(x²-2xy+y²)

    = x²+2xy+y²+x²-2xy+y²

    = 2x²+2y²

    = 2(x²+y²)

    b, 2(x–y).(x+y)+(x+y)²+(x–y)²

     = 2(x²-y²)+2(x²+y²)

     = 2x²-2y²+2x²+2y² 

     = 4x²

    c, (x–y+z)²+(z–y)²+2(x–y+z).(y–z) 

    = (x–y+z)²– 2(x-y+z)(z-y)+(z-y)²

    = (xy+zz+y

    = x²

    0
    2021-08-31T06:21:32+00:00

    a; ( x+y)^2+(x-y)^2

    =>x^2+2xy+y^2+x^2-2xy+y^2

    =>2x^2+2y^2

    =>2(x^2+y^2)

    b;2(x-y)(x+y)+(x+y)^2+(x-y)^2

    =>2(x^2-y^2)+2(x^2+y^2)

    =>2x^2-2y^2+2x^2+2y^2

    =>4x^2

    c;=>x^2-y^2+z^2+z^2-2zy+y^2+2x-2y+2zy-2z^2

    =>x^2 -2x+2y

    câu c mk ko chắc lắm ^^

    #chúc bn học tốt 

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )